Strategi Untuk Meningkatan Laba Usaha Tani Cengkeh Di Desa Tigawasa - Erliyani, Putu; Atmadja, Anantawikrama Tungga (Universitas Pendidikan Ganesha, 2025)
The formulation of the problem in this study is that clove farmers in Tigawasa Village cannot calculate financial reports from the results of clove sales each year and clove farmers in Tigawasa Village do not know the right strategy to increase profits. The purpose of this study is to find out the income statement that should be compiled by clove farmers and to find out the strategies that can be carried out in increasing the clove farming profit in Tigawasa Village. The number of samples in this study was 10 clove farmers in Tigawasa Village, and the population of this study were all clove farmers in Tigawasa Village. The research method used in this study was a qualitative research method, the results of this study showed that clove farmers could not calculate the income statement from the sale of cloves so far and clove farmers did not know how to increase their clove farming profits.